2007
DOI: 10.1139/z06-201
|View full text |Cite
|
Sign up to set email alerts
|

A flyway perspective of foraging activity in Eurasian Green-winged Teal,Anas crecca crecca

Abstract: Time-activity budgets in the family Anatidae are available for the wintering and breeding periods. We present the first flyway-level study of foraging time in a long-distance migrant, the Eurasian Green-winged Teal, Anas crecca crecca L., 1758 (''Teal''). Behavioral data from early and late spring staging, breeding, and molting sites were collected with standardized protocols to explore differences between the sexes, seasons, and diel patterns. Teal foraging activity was compared with that of the Mallard, Anas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…The breeding period of dabbling ducks, however, may not be as easily adapted to seasonal changes in food abundance at the breeding site. One important reason is that any such adaptation has to be traded off against selective pressures acting in other biomes and at other times of the annual cycle (Arzel et al, 2007(Arzel et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…The breeding period of dabbling ducks, however, may not be as easily adapted to seasonal changes in food abundance at the breeding site. One important reason is that any such adaptation has to be traded off against selective pressures acting in other biomes and at other times of the annual cycle (Arzel et al, 2007(Arzel et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…This result, combined with other metrics, lends further support to the conclusion that Lesser Scaup were burdened with increased energetic demands that they were not able to overcome by the time the late migration progressed in our study area in 2013. These results suggest that Lesser Scaup may conform more to a "capital migrant" strategy (sensu Arzel et al 2007), relying more on carrying a larger balance of lipid reserves acquired during winter (Anteau and Afton 2004;Herring and Collazo 2006) and opportunistically during migration (Esler et al 2001;Anteau and Afton 2009) but less prone to recovering from losses associated with energetically demanding environmental or migration conditions. It is also plausible that forgoing lipid accumulation altogether was a strategy in and of itself among migrating Lesser Scaup during the coldest and latest year to try to minimize possible trade-offs with wing loading or navigation associated with high lipid burdens (Lima 1986), although migrants would still have to meet minimum lipid balances necessary to complete migration and breeding, which tend to limit clutch size and reproduction in Lesser Scaup (Afton and Ankney 1991) and other ducks (Ankney et al 1991).…”
Section: Discussionmentioning
confidence: 91%
“…Such a diet shift could explain the maintenance of lipids in that year and the concomitant decline in protein because high intake of invertebrate-rich diets has been associated with increases in protein masses in ducks (Alisauskas et al 1990; Barzen and Serie 1990;Alisauskas and Ankney 1994). This adaptive dietary intake to focus on maintaining the same relative reserve of lipids seems consistent with an "income migrant" strategy (sensu Arzel et al 2007) where migrants adjust foraging to meet demands encountered en route rather than relying on stores built up at previous stopovers or wintering areas. Lesser Scaup followed a pattern similar to that of Blue-winged Teal with protein reserves, but all other metrics notably contrasted between the two species.…”
Section: Discussionmentioning
confidence: 93%
“…During the breeding season, however, they have access to an overabundance of boreal lakes, leading to low densities of birds per wetland and to many suitable sites remaining unused (Elmberg et al 2005). In a related study, Arzel et al (2007) found a positive relationship between teal foraging time and densities of both teal and other dabbling ducks. This is consistent with the idea that food is not limiting; alternatively, it could indicate that teal offset costs of higher food competition for benefits of improved predator vigilance and dilution effects provided by larger flocks (Guillemain et al 2002.…”
Section: Flyway Patterns Of Food Abundancementioning
confidence: 82%